ANALISIS POTENSI BAHAYA DAN RISIKO MENGGUNAKAN METODE JOB SAFETY ANALYSIS PADA AKTIVITAS PENCUCIAN DI PT. ANUGRAH BORNEO MARUYA PERSADA KABUPATEN KETAPANG KALIMANTAN BARAT - Oktavianus, Oktavianus; Murad, Murad; Setiawati, Septami (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2024)
PT. Anugerah Borneo Maruya Persada carries out mining through excavation, transportation and washing, during the washing process in the Washing Plant area there are still conditions work that can be categorized as unsafe. Therefore, it is necessary to identify risks, risknassessmentcand risknrecommendations using the Job Safety Analysis method for Prevent work accidents among workers who are active in the Washing Plant 1 location and Washing Plant 2 at PT. Borneo Maruya Persada Award. Results obtained from research namely, there is a risk assessment before and after control recommendations are carried out decrease. On equipment activities at Washing Plant 1 before recommendations are made controlnhas 8% HighnRisk, 44% Moderate Risknand 48% Low Risk. Once done controlnrecommendations are 0% High Risk, 7% Moderate Risk and 93% Low Risk.Meanwhile, equipment operating activities at Washing Plant 2 are before the recommendation control of 10% High Risk, 50% Moderate Risk and 40% Low Risk. Once done Control recommendations are 0% High Risk, 10% Moderate Risk and 90% Low Risk.Keywords: HIRARC, JSA, Risk Management